DESIGNING A CONTEXT-AWARE MATERNAL HEALTH INFORMATION SYSTEM FOR RURAL MIDWIVES: A NEEDS ASSESSMENT IN COASTAL COMMUNITIES OF GRESIK - Anwar Sadad; Elies Meilinawati SB; Fatati Larasati (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Village midwives are at the forefront of maternal health services, yet they often face overwhelming administrative burdens due to manual recording and reporting systems. The transition to digital health applications is essential, but it must be tailored to the specific infrastructural and usability contexts of rural and coastal areas to ensure high adoption rates. This study aims to explore the context of use, identify operational bottlenecks in current manual practices, and define the functional requirements for a proposed maternal health application designed for midwives in coastal and rural settings. A descriptive quantitative approach was utilized. Data were collected via a structured questionnaire from 8 frontline healthcare workers, predominantly village midwives (87.5%), operating within the working area of  Ujungpangkah Public Health Center, Gresik, Indonesia. The survey assessed current data management practices, infrastructural constraints, and digital feature preferences. The findings reveal a 100% reliance on physical register books for initial data entry, with 75% of respondents utilizing manual, paper-based reporting. The most significant bottlenecks identified were the redundancy of manual data re-entry (75%) and the universal difficulty in monitoring high-risk pregnancies (100%). Furthermore, 50% of the respondents experience unstable internet connectivity. Consequently, users strongly demanded automated monthly reporting (100%), robust data search capabilities (100%), and an offline-first architecture (75%). Previous digital solutions were criticized for overly complex interfaces (62.5%). To effectively support maternal health monitoring and reduce administrative fatigue, digital interventions for rural midwives must prioritize offline capabilities, automated data recapitulation, and a highly simplified, intuitive user interface tailored to regional infrastructural realities.